Effect of the Fabrication Technique on Compressive Properties of Cu-PTFE Composites - Xuezhi Tang; Zhijun Wang; Jianping Yin; Jianya Yi (Advances in Materials Science and Engineering)
In this paper, the effect of manufacturing methods on the compressive properties of Cu-PTFE (polytetrafluoroethylene) composites was investigated. Two types of specimens were prepared through different manufacturing methods (extrusion forming and hot-press sintering). The specimens were tested using an electrohydraulic press and split-Hopkinson pressure bars for quasi-static loading and dynamic impact, respectively. The specific fracture processes were recorded by using a high-speed camera, and the failure microstructures of the specimens were analysed by SEM. According to the results, hot-press sintered specimens have consistently higher strength and toughness under dynamic compression than the extruded specimens, while the mechanical properties of hot-press sintered specimens are inferior to those of extruded specimens under quasi-static compression. The failure of extruded specimens is primarily caused by the elastic mismatch between the PTFE matrix and Cu particles, as well as the polymerisation of plastic pores, which leads to particle pullout. However, the cracks in the hot-press sintered specimens were caused by the shear deformation and interface sliding of the PTFE matrix, which led to matrix tearing.